2005
DOI: 10.2170/jjphysiol.r2120
|View full text |Cite
|
Sign up to set email alerts
|

Manual Acupuncture Needle Stimulation of the Rat Hindlimb Activates Groups I, II, III and IV Single Afferent Nerve Fibers in the Dorsal Spinal Roots

Abstract: Using single unit nerve recording techniques in rats, the present experiment aimed to determine which specific population of afferent nerve fibers (groups I, II, III and IV) in the dorsal roots at the 4th or 5th lumbar segments (L4 or L5) are activated during manual acupuncture needle stimulation. An acupuncture needle 300-340 microm in diameter was inserted into the skin and underlying muscles around the Zusanli acupoint (ST36) area in the hindlimbs, and was manually rotated right and left at a frequency of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 24 publications
1
63
0
Order By: Relevance
“…47 Previous studies also identified that MA could activate I, II, III and IV afferent fibers. [64][65][66][67] In the present work, stimulation by MA manipulation at an intensity of 2 Hz is sufficient to activate Ad-and C-fibers. 66 The stimulatory effects of MA at ST37 on distal colonic motility could be inhibited in part by pretreatment of A-fibers with cobra venom, an A-selective demyelination agent.…”
Section: Discussionmentioning
confidence: 99%
“…47 Previous studies also identified that MA could activate I, II, III and IV afferent fibers. [64][65][66][67] In the present work, stimulation by MA manipulation at an intensity of 2 Hz is sufficient to activate Ad-and C-fibers. 66 The stimulatory effects of MA at ST37 on distal colonic motility could be inhibited in part by pretreatment of A-fibers with cobra venom, an A-selective demyelination agent.…”
Section: Discussionmentioning
confidence: 99%
“…Insertion and manual or electrical stimulation of needles in skin and muscle activates A␣, ␤, ␦, and C fibers (49). In particular, activation of A␦ and C fibers may be essential for modulating autonomic nervous system activity (90).…”
Section: Acupuncturementioning
confidence: 99%
“…14 However, single unit nerve recording techniques in rats has shown that acupuncture needle stimulation activates all types of single afferent nerve fibres (ie, groups I, II, III and IV). 15 It is also likely that autonomic and motor efferents are involved too because of the wide variety of clinical, physiological and psychological effects observed during and after acupuncture stimulation.…”
Section: Physiological Intention Of Needlingmentioning
confidence: 99%